Burma beyond the elections: Economic perspectives and recommendations for an EU policy shift - Christine Schuster; Gerhard Will (Stiftung Wissenschaft und Politik (SWP), 2010)
With its announcement of democratic elections to be held on 7 November 2010, Burma's military regime has set the topic that is absolutely dominating national and international discussion of the country's political future. Problems facing Burma's economic development have taken on a position of much lower importance in this discussion, although there are obvious deficits in this area. The country's enormous economic potential continues to be largely wasted rather than systematically exploited. In past months, the military has announced a series of economic policy changes, but achieving a true turnaround with genuinely positive impacts would necessitate a large number of more profound changes that could only be achieved along a longer timeframe. In this respect, the EU and other international actors can provide important contributions if they stop making their support of Burma contingent on political preconditions. Instead, they should act according to the principle that economic consolidation can be understood as a fundamental prerequisite for political transformation
Keywords: 320